1997
DOI: 10.1089/dna.1997.16.485
|View full text |Cite
|
Sign up to set email alerts
|

The Promoter Activity of the Phospholipase C-γ2 Gene Is Regulated by a Cell-Type-Specific Control Element

Abstract: We have cloned and characterized a genomic DNA spanning the 5'-flanking region, the first and second exons, and the first intron of the human PLC-gamma2 gene. The proximal upstream region is highly GC-rich and lacks a TATA box, whereas the distal region contains several AT-rich tracts. Multiple transcription initiation sites were identified by primer extension analysis. Based on the transient transfection assays, the major transcriptional activation element was identified between -183 and +43 (G2SE) and a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…So far, the promoter regions of PLCγ1, γ2, and β3 have been isolated [19–22], and it has been reported that these regions are GC‐rich and have no TATA box. We also noticed that the promoter region of PLCδ4 is GC‐rich and has no TATA box, indicating that these properties are common among the PLC isozymes.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the promoter regions of PLCγ1, γ2, and β3 have been isolated [19–22], and it has been reported that these regions are GC‐rich and have no TATA box. We also noticed that the promoter region of PLCδ4 is GC‐rich and has no TATA box, indicating that these properties are common among the PLC isozymes.…”
Section: Resultsmentioning
confidence: 99%
“…Daudi (human Burkitt lymphoma) cells (1-2 × 10 7 ) were electroporated with 20 µg of plasmid DNA as described (Lee et al, 1997). After 48 hrs of incubation, the cells were harvested and soluble, cytosolic extract was prepared by three cycles of freezing-thawing.…”
Section: Cell Culture Transient Transfection and Cat Assaysmentioning
confidence: 99%
“…After 48 hrs of incubation, the cells were harvested and soluble, cytosolic extract was prepared by three cycles of freezing-thawing. The CAT activities were assayed with 100-150 µg of the extracts as described previously (Lee et al, 1997).…”
Section: Cell Culture Transient Transfection and Cat Assaysmentioning
confidence: 99%
See 1 more Smart Citation